(+)-Borneol inhibits the generation of reactive oxygen species and neutrophil extracellular traps induced by phorbol-12-myristate-13-acetate - Chen, Hanze; Xu, Xinxin; Tang, Qiwen; Ni, Linhui; Cao, Shuxia; Hao, Yonggang; Wang, Li; Hu, Xingyue (Frontiers in Pharmacology, 2022)
Background and Purpose: Neutrophil extracellular traps (NETs) are special web-like structures that can be generated in both infectious and noninfectious diseases. Previous studies showed that reactive oxygen species (ROS) were crucial in NETosis. The purpose of this study is to evaluate the effect of (+)-borneol, an antioxidant, on NETosis. Methods: Human neutrophils were stimulated with phorbol-12-myristate-13-acetate (PMA) to induce NETs. Neutrophils pre-treated with (+)-borneol before PMA stimulation were used to examine the effect of (+)-borneol on NETosis. The ROS generation of neutrophils was also measured to explore the potential mechanism. Results: (+)-Borneol pre-treatment inhibited the NETosis induced by PMA. Immunofluorescence staining visualized and confirmed the inhibitory effect. (+)-Borneol inhibited the burst of ROS in neutrophils caused by PMA. Suppressing NADPH oxidase or protein kinase C (PKC) eliminated the effect of (+)-borneol on NETosis. Moreover, inhibiting Toll-like receptor 2 (TLR2) led to increased NETosis which can be inhibited by (+)-borneol. Conclusion: (+)-Borneol decreases the ROS level in activated neutrophils and inhibits the NETosis triggered by PMA stimulation in vitro. (+)-Borneol therapy may be effective in some NETs-dependent conditions.